2021
DOI: 10.1111/and.14139
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between single polymorphic variants of the mitochondrial nicotinamide adenine dinucleotide dehydrogenase 3, and 4L (MT‐ND3andMT‐ND4L) and male infertility

Abstract: Male infertility is a multifactorial condition associated with different genetic abnormalities in at least 15%–30% of cases. The purpose of this study was to identify suspected correlations between infertility and polymorphisms in mitochondrial NADH dehydrogenase subunits 3 and 4L (MT‐ND3 and MT‐ND4L) in subfertile male spermatozoa. Sanger sequencing of the mitochondrial DNA target genes was performed on 68 subfertile and 44 fertile males. Eight single nucleotide polymorphisms (SNPs) in MT‐ND3 (rs2853826, rs28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Dysbiosis-induced dysregulation of the intestinal flora also causes decreased expression of the Ggnbp2 gene, which is crucial for repairing meiotic DNA double-strand breaks in spermatocytes, consequently inhibiting spermatogenesis 34 . Moreover, reduced expression of the genes encoding core subunits of the respiratory chain on mitochondrial membranes, including MT-ND1, MT-ND2, MT-ND4, MT-ND5 and MT-ND4L, leads to increased sperm mitochondrial membrane potential and decreased sperm motility 35 37 . Furthermore, the diminished expression of the Crisp2 gene, essential for regulating Ca 2+ influx during sperm capacitation and motility, has adverse effects on sperm motility 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Dysbiosis-induced dysregulation of the intestinal flora also causes decreased expression of the Ggnbp2 gene, which is crucial for repairing meiotic DNA double-strand breaks in spermatocytes, consequently inhibiting spermatogenesis 34 . Moreover, reduced expression of the genes encoding core subunits of the respiratory chain on mitochondrial membranes, including MT-ND1, MT-ND2, MT-ND4, MT-ND5 and MT-ND4L, leads to increased sperm mitochondrial membrane potential and decreased sperm motility 35 37 . Furthermore, the diminished expression of the Crisp2 gene, essential for regulating Ca 2+ influx during sperm capacitation and motility, has adverse effects on sperm motility 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studying genetic variations such as SNPs might be a helpful genetic analysis to understand the molecular bases of idiopathic infertility in males. In many studies, certain SNPs have shown an association with certain disorders such as cancer and infertility [24]. This work aimed to investigate whether there was an association between polymorphisms in the mitochondrial genes MT-CO3, MT-ATP6 and MT-ATP8 and male subfertility.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatozoa with defective mitochondria produce insufficient ATP and have elevated levels of reactive oxygen species (ROS) or free radicals. In an imbalanced system, the production of ROS and free radicals would cause significant damage to the mitochondria and mtDNA, affecting sperm motility and finally leading to male infertility [ 24 ]. More specifically, an inadequate molecular profile of all types of male infertility still remains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we scanned sterile and fertile males for polymorphisms by the direct sequencing of MTND3 , MTND4L , and MTND4 genes in our laboratory [ 108 ].…”
Section: Mitochondrial Genome Mutations/variations and Male Infertilitymentioning
confidence: 99%